The impact of levothyroxine sodium treatment on oxidative stress in Hashimoto's thyroiditis. Issue 6 (June 2016) - Ates, Ihsan; Altay, Mustafa; Yilmaz, Fatma Meric; Topcuoglu, Canan; Yilmaz, Nisbet; Berker, Dilek; Guler, Serdar
Abstract : Objective: Although several studies reported increased oxidative stress in Hashimoto's thyroiditis (HT), the effect of levothyroxine treatment on oxidative status is not studied extensively. Therefore, we conducted this study to investigate the effects of levothyroxine replacement on oxidative stress in HT. Design and methods: Thirty-six patients recently diagnosed with HT-related hypothyroidism and 36 healthy controls were included in the study. Levothyroxine replacement was started to patients with hypothyroidism, and had been followed-up for 6 months. Results: Mean basal serum total antioxidant status (TAS), total thiol, arylesterase, and paraoxonase 1 (PON1) levels were significantly lower, and serum total oxidant status (TOS) and oxidative stress index (OSI) were significantly higher in the patients with hypothyroid than the controls. In the hypothyroid group serum TAS, total thiol, arylesterase, and PON1 levels increased and serum TOS and OSI levels decreased significantly after levothyroxine treatment. Pretreatment serum TAS, total thiol, PON1, and arylesterase levels were positively correlated with free levothyroxine (fT4 ) and negatively correlated with thyroid-stimulating hormone (TSH), antithyroid peroxidase (anti-TPO), and antithyroglobulin (anti-TG) levels. Also, pretreatment serum TOS and OSI levels were negatively correlated with fT4 levels and positively correlated with TSH, anti-TPO, and anti-TG. We have also found that the fT4 and anti-TPO levels are independent predictors of the oxidative stress parameters in stepwise multivariable linear regression analysis. Conclusion: This study suggests that levothyroxine replacement decreases oxidant status and increases antioxidant status following the 6 months of levothyroxine replacement in hypothyroidism that develops in accordance with the HT.